Metagenomic Profiling of Gut Microbiome Signatures Across Liver Disease Stages and HCV-Related Hepatocellular Carcinoma in Egyptian Patients - Zahra, Marwa A (AUC Knowledge Fountain, 2026)
Dysbiosis in the gut microbiome, particularly concerning the synchronous crosstalk between the gut and the liver, has been associated with various diseases. This study profiles the gut microbiome in liver diseases among Egyptian patients, with a focus on the hepatitis C virus (HCV) and hepatocellular carcinoma (HCC), both of which are highly prevalent in Egypt. Utilizing shotgun metagenomic sequencing, we analyzed microbial gene catalogs and taxonomic profiles from 46 Egyptian patients categorized into five groups: healthy individuals, liver disease patients of different etiologies, post-HCV, treated HCV, and HCV-HCC patients. Healthy and treated HCV patients exhibited distinct microbial profiles characterized by an abundance of beneficial bacteria, Faecalibacterium and Bifidobacterium (p < 0.05), associated with anti-inflammatory shortchain fatty acid production. Conversely, liver disease and HCC patients displayed increased pathogenic bacteria, Escherichia (p < 0.05), and genes linked to inflammation and oncogenesis, including lipopolysaccharide biosynthesis. These findings suggest a dominance of Faecalibacterium in healthy Egyptians, likely attributable to fiber-rich diets, and cytochrome P450 genes as potential HCC biomarkers, possibly connected to aflatoxin exposure. Treated HCV patients showed significant microbiome recovery, reflecting effective antiviral therapy. These findings emphasize that Egypt-specific factors, such as persistent resistance genes post-HCV due to antibiotic use and the prominence of bile acid metabolism genes, are influenced by high HCV prevalence and environmental exposures like aflatoxins. Taken together, the results highlight the need for region-specific microbiome research priorities in Egypt and underscore how local dietary, clinical, and environmental factors may shape future objectives in understanding liver disease pathogenesis and prevention.